Development and validation of a RP–HPLC method for the quantitation studies of fipronil in Parakill suspensions - Elena Gabriela Oltean; Nica, A. (Medicamentul Veterinar, 2011)
An isocratic high-performance liquid chromatography (HPLC) procedure was developed for the quantitative determination of fipronil in suspensions of Parakill. HPLC separation was carried out by reversed phase chromatography on Betasil C18 (250 mm x 4.6 mm i.d.; 5 μm particle size), held in thermostat at 25°C. The mobile phase consisted of Acetonitrile/ Distilled water (60/ 40 v/ v), with a flow rate of 1 ml/ min and with UV detection at 220 nm. In order to validate the method, the following parameters have been investigated linearity (r2=0.9999), range, precision, accuracy, specificity, limit of detection and limit of quantification. The described method can be successfully applied for the analysis of the active pharmaceutical compound in PARAKILL suspensions.